(untitled) (International Journal of Engineering and Computer Science, 2017)
For information retrieval, the search engine plays a key role while Users may not always experience the right/appropriate results at the beginning of the search. Such irrelevance is largely due to the enormous variety of user’s contexts and backgrounds as well as the ambiguity of texts.. However when the same query is submitted by different users most search engines return the same results regardless of who submits the query. In general each user has different information needs for his/her query. Hence there is a need of creating the personalized web search. Personalized web search (PWS), which has its effectiveness in improving the quality of various search services on the Internet. However, users’ are reluctant to disclose their private information during search. Hence it has become a major barrier for the wide proliferation of PWS. The proposal of PWS framework called UPS has adaptively generalized the profiles by queries while respecting user specified privacy requirements. The Use of MP model in this project creates the privacy element and at the same time it gives us the relevancy between the websites. This personalized web search creates the user oriented effective navigation